SINGLE NUCLEOTIDE POLYMORPHISM DETECTION AND SEQUENCE CHARACTERIZATION OF BETA CASEIN GENE IN BUNAJI AND FRIESIAN-BUNAJI CROSSBRED COW - Dubagari, Nkpusireufu Gambo; Mwagu, B. I.; Ojo, O. A. (FUDMA JOURNAL OF SCIENCES, 2022)
Milk is an important food constituent in diet. This study was undertaken to detect the presence of SNP in βcasein gene of Bunaji and Friesian X Bunaji crossbred cows using sequencing. 60 animal comprising of 30 Bunaji and 30 friesian X Bunaji cows were understudy. DNA was extracted from 200 μl of the blood using high salt method. The electrophoresis revealed molecular DNA with a single band. The exon 7 of βcasein gene was amplified by PCR using published primer. 20 amplicon were sent for sequencing, 10 each for Bunaji and Friesian X Bunaji crossbred. The DNA sequence of exon 7 of beta casein gene were aligned using the MAFFT online sequence alignment tools. The results revealed, 6 polymorphic sites at exon 7 beta casein gene. The SNP were at positions; 221, 350, 381, 387, 510, 387 and 516. Four of the SNPs were nonsynonymous in nature while 2 were synonymous. A nucleotide substitution from C→A was observed in Bunaji and its crossbred counterpart resulted in substitution of amino acid proline → histidine; and C→G substitution resulting in a Serine → Arginine substitution implying that Bunaji and Friesian X Bunaji had the preponderance of A2, A1 and B variant, resulting in potentials release of bioactive peptide upon digestion of A1 and B variant. SNPs discovered in this study can be used as molecular genetic markers for marker assisted selection (MAS) to increase the rate of genetic improvement of milk production traits in Bunaji and Friesian Bunaji crossbred cows